Experiences of intensive home treatment for a mental health crisis during the perinatal period: A UK qualitative study. (20th August 2020) - Rubio, Luisa; Lever Taylor, Billie; Morant, Nicola; Johnson, Sonia
Abstract: Some women with severe perinatal mental health difficulties in England are cared for by acute home treatment services, known as Crisis Resolution Teams (CRTs), which provide short‐term home‐based treatment for adults experiencing a mental health crisis. Intensive home treatment has been trialed in a number of countries, but it is not known how well suited it is to the needs of perinatal women. This qualitative study aimed to explore how women and practitioners experience the provision of intensive home treatment for perinatal mental health problems. Semi‐structured interviews were conducted with women who had received intensive home treatment in the perinatal period ( n  = 15), and focus groups were held with practitioners working in CRTs or in specialist perinatal mental health services (3 groups, n  = 25). Data were analysed thematically. Women commonly found intensive home treatment problematic, experiencing it as intrusive and heavily risk‐focused, with poor staff continuity and little tailoring to the perinatal context. However, women valued emotional support when provided, particularly when it had a perinatal focus, sometimes based on practitioners sharing their own experiences. Some women also appreciated avoiding hospital admission, but choice was often limited. Practitioners reported a lack of perinatal training among CRT staff and described difficulties tailoring treatment to perinatal women's needs. Currently, intensive home treatment, as offered by CRTs, may not be well suited to women with perinatal mental health difficulties. Findings suggest a need to develop community crisis responses that are better tailored to the needs of this population.